Public perception toward and identification of pengkid : a case Study of people in Negeri Sembilan - Dzulkifli, Mariam Adawiah; Rokis, Rohaiza; Abdul Rahim, Adibah (2012)
Pengkid is a term used to refer to a female, whose physical and behavioural appearances resemble those of a male. Her sexual orientation is also towards other females; in other words, preferring same-sex partners. This group of people (pengkid) is becoming more visible in society and lately they have been associated with a number of social concerns such as abduction, drugs, and sexually related problems. With the awareness that the problems associated with pengkid are now becoming a serious social disease, an empirical study is needed to understand pengkid and the public’s perception towards them. This study was conducted to know the perception of the public towards pengkid, and to come up with indicators for the purpose of identifying pengkid. Another objective is to understand factors contributing to the increased number of pengkid. A combination of quantitative and qualitative research methods was used. A survey involving a total of 1,298 samples represented people in three main districts in Negeri Sembilan i.e. Seremban, Port Dickson and Rembau. In addition, structured interviews were also conducted with several target groups or subject matter experts such as religious figures, academicians, lawyers, medical doctors, social workers as well as pengkid themselves. The main finding from the research indicates that the public’s level of awareness of the pengkid problem is high. In addition, the research is also able to identify physical and behavioural indicators of pengkid and the factors thought to contribute to the spreading of the pengkid problems.